Development of Science Learning Achievement and Problem-Solving Thinking by STEM Education Management with Engineering Design Process for Grade Six Students - Kulabkaeo, Atitaya; Suwankitti, Sasiwan; Saengloetuthai, Jittirat (Journal of Research and Curriculum Development, 2023)
This research aimed to compare the science learning achievement of students before and after learning through STEM education management with Engineering is Elementary, in order to compare the problem-solving and thinking ability of students before and after learning through STEM education management with Engineering is Elementary, and studying the satisfaction of the students with STEM education management with Engineering is Elementary. The research sample consisted of 29 Grade Six students studying in the first semester of the 2022 academic year, obtained by cluster sampling. The research instruments were lesson plans, achievement tests, problem-solving thinking tests, and a satisfaction questionnaire. The statistics used in data analysis included mean, standard deviation, and a dependent t-test. The results showed that the science learning achievement and problem-solving and thinking abilities of the students after learning through STEM education management with Engineering is Elementary are higher than that of before learning with the statistical significance at a level of .05. Overall, the students were satisfied with the STEM education management with Engineering is Elementary at a high level.